Competitiveness in the CFA Franc Zone - Tsangarides, Charalambos (IMF Working Papers; Working Paper, 2007)
This paper reviews the evolution of competitiveness in the CFA franc zone using a proposed comprehensive competitiveness framework. In particular, we examine competitiveness in the WAEMU and CEMAC regions by analyzing the "environment" and "policy" components of competitiveness and their quantifiable determinants, including indicators to measure productivity and labor market conditions, prices and costs, macroeconomic performance, business environment, governance, and technology and infrastructure. Our findings suggest that despite some recent improvements-particularly for the CEMAC-both regions face serious competitiveness challenges when compared to pier groups of countries. In order to become more competitive, raise growth, and improve the quality of life, there is a need for structural reform to improve productivity, reduce factor costs, and create the right business, legal, and political environment to attract economic activity.